Usia, Pendidikan, dan Penggunaan Aplikasi Kesehatan Berhubungan dengan Penerimaan Penggunaan Aplikasi Deteksi Penyakit Kronis - Widianawati, Evina; Kusumawati, Nugraheni; Wulan, Widya Ratna; Pantiawati, Ika (Health Information : Jurnal Penelitian, 2023)
The results of the examination of patients who take part in the Prolanis program are only recorded at health care facilities, while the patients themselves do not know the results of the examination. To bridge this, chronic disease detection applications are designed. There are several factors that can affect a user's willingness to use the application, one of which is the user's characteristics. This study aims to examine the relationship between respondent characteristics and acceptance of chronic disease detection applications. The type of research used is quantitative research with the location of the study, namely in health service facilities in Semarang Regency, namely Lerep Health Center, Ungaran Health Center and Niki Helti Clinic. Data were obtained through questionnaires with a linkert scale filled out by patients in health care facilities as system users as many as 131 respondents. The study will be conducted in June-August 2023. Data analysis techniques using Chi square test and Spearman Rank test. The results showed that there was a relationship between age (p value 0.001), education (p value 0.000), length of use of mobile phones (p value 0.001) and use of health applications (p value 0.012) on the acceptance of chronic disease detection applications. Gender (p value 0.051), occupation (p value 0.626) and length of work (p value 0.293) were not associated with acceptance of chronic disease detection applications. In further research, it is recommended to conduct a mix method study, apply a qualitative approach, and add variables such as digital literacy.